“Bringing new life in”: Hope as a know-how of not knowing - Cuffari, Elena; Fourlas, George; Whatley, Maceo (Frontiers in Psychology, 2022)
We offer a theoretical and empirical exploration of parental or guardian hope through an enactive, ecological, and reflective lifeworld research framework. We examine hoping as a practice, or know-how, by exploring the shape of interviewees’ lives as they prepare for lives to come. We pursue hoping as a necessarily shared practice—a social agency—rather than an individual emotion. One main argument is that hoping operates as a kind of languaging. An enactive-ecological approach shifts scholarly conversations around hope, in part by including voices of non-scholars and considering lifeworld factors like class privilege. We aim to identify particular impediments to or facilitators of hope, which may be thought of as classes of restrictive and generative thought-shapers, respectively. Results from our qualitative study indicate that uncertainty is deeply salient to hoping, not only because hope as a concept entails epistemic limits, but more vitally because not knowing, when done skillfully and when supported through education and some degree of socio-economic security, leaves room for others to reframe utterances, and so for the family or community to resist linguistic enclosure.